2006
DOI: 10.1007/s10597-006-9050-y
|View full text |Cite
|
Sign up to set email alerts
|

Treating Homeless Clients with Severe Mental Illness and Substance Use Disorders: Costs and Outcomes

Abstract: This study compared the costs and outcomes associated with three treatment programs that served 149 individuals with dual disorders (i.e., individuals with co-occurring severe mental illness and substance use disorders) who were homeless at baseline. The three treatment programs were: Integrated Assertive Community Treatment (IACT), Assertive Community Treatment only (ACTO), and standard care (Control). Participants were randomly assigned to treatment and followed for a period of 24 months. Clients in the IACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
134
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 36 publications
2
134
0
4
Order By: Relevance
“…21,37,38 Although the study by Drake and colleagues found evidence that individuals involved in ACT reported decreased substance use on some measures relative to individuals in the control condition, 2 recent investigations tested an enhanced form of ACT that included ACT staff with expertise in treating substance use and did not find evidence that these enhancements were associated with superior outcomes for substance abuse. 21,37,38 Specifically, Essock et al 38 compared the enhanced ACT condition with an intense clinical case management program that also had dual diagnosis expertise and did not find evidence for differences across groups on substance abuse outcomes. Likewise, Morse et al 21 compared ACT with substance abuse expertise (so-called integrated ACT) with ACT alone and with standard care and also failed to find differences in substance use across conditions.…”
Section: Port Psychosocial Treatment Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…21,37,38 Although the study by Drake and colleagues found evidence that individuals involved in ACT reported decreased substance use on some measures relative to individuals in the control condition, 2 recent investigations tested an enhanced form of ACT that included ACT staff with expertise in treating substance use and did not find evidence that these enhancements were associated with superior outcomes for substance abuse. 21,37,38 Specifically, Essock et al 38 compared the enhanced ACT condition with an intense clinical case management program that also had dual diagnosis expertise and did not find evidence for differences across groups on substance abuse outcomes. Likewise, Morse et al 21 compared ACT with substance abuse expertise (so-called integrated ACT) with ACT alone and with standard care and also failed to find differences in substance use across conditions.…”
Section: Port Psychosocial Treatment Recommendationsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] In turn, individuals assigned to the ACT condition used fewer emergency services and more outpatient services, including financial and housing assistance, relative to individuals in the control conditions. 13,14,16,19,23 A few studies also found that individuals assigned to the ACT condition reported decreased symptomatology, 17,20,22,24,25 increased medication adherence, 10,17 more contact with the treatment team, 23,26 more days in stable community housing, 7,12,13,17,19,21,25 and greater satisfaction with treatment among patients and their family members relative to the control condition.…”
Section: Port Psychosocial Treatment Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations